Sacred Nexus of Nepal in Hindu Mythology: Representation and Significance in Sanskrit Scriptures - Adhikary, Ramesh Prasad (Academia Research Journal, 2024)
This research investigates the representation of Nepal in Hindu mythology and its significance within Sanskrit scriptures, positioning the country as a pivotal spiritual center for Hindus. Nepal, often celebrated in texts such as The Vedas, Puranas, The Ramayana, and The Mahabharata, serves as a crucial element of Hindu cosmology, where its sacred geography and cultural heritage converge. The primary objective of this study is to analyze how Nepal is depicted in key Hindu texts, exploring its associations with major deities, saints, and pilgrimage sites, and to understand its enduring importance in Hindu spirituality. The methodology employed combines qualitative textual analysis and historical interpretation, drawing from both primary and secondary sources. Primary sources include significant Sanskrit scriptures, while secondary sources encompass scholarly articles and commentaries that contextualize Nepal’s mythological and cultural relevance. The findings reveal that Nepal is portrayed as a land of divine manifestations, particularly linked to deities such as Lord Shiva and various Rishis. The study highlights important pilgrimage sites, such as Pashupatinath and Swayambhu, which have historically attracted devotees, thus reinforcing Nepal’s role as a center of spiritual practices and rituals. Furthermore, the research underscores the interconnectedness of Nepal with the broader narratives of Bharatvarsha, contributing to its characterization as a sacred domain. In conclusion, this research enhances the understanding of Nepal’s mythological significance and its historical and contemporary relevance as a spiritual center within Hinduism. It invites further exploration into the intricate relationship between geography, spirituality, and cultural identity in Hindu traditions, emphasizing the need for ongoing scholarly attention to Nepal’s rich spiritual heritage.